Fine cellulose fiber

JP2025021934APending Publication Date: 2025-02-14MARUSUMI PAPER
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023126052
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0009】 本発明の微細セルロース繊維は、その分散液をわずかに振盪することで粘度が低下するため、取扱性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021934000004
    Figure 2025021934000004
  • Figure 2025021934000005
    Figure 2025021934000005
  • Figure 2025021934000001
    Figure 2025021934000001
Patent Text Reader

Abstract

To provide a fine cellulose fiber which is excellent in handleability.SOLUTION: A fine cellulose fiber is formed by making cellulose fibers fine, wherein at least a part of hydroxyl groups of the fine cellulose fibers is substituted with a sulfuric ester group, when 100 g of 1 mass% aqueous dispersion of the fine cellulose fiber is sealed in a centrifugal settling tube with a volume of 100 mL, is left standing at 20°C for 24 hours, then is shaken at 20°C and 300 rpm for 5 minutes or more in an approximately horizontal direction, then is rotated at 20°C and 1 rpm for 3 minutes using a B-type viscometer and is measured, viscosity μ1 is 100,000 mPa s or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fine cellulose fibers. [Background technology]

[0002] Cellulose nanofibers (CNF) are microfibers with a fiber width of several to tens of nm and a fiber length of several hundred nm, which are made by nano-processing (mechanical fiberization, TEMPO catalytic oxidation, etc.) plant-derived cellulose. CNFs are lightweight, highly elastic, high strength, and have low linear thermal expansion. For this reason, composite materials containing CNFs are expected to be used in a variety of fields, including not only industrial fields but also food and medical fields.

[0003] When mechanically defibrating CNF, a large amount of energy is required to obtain CNF because the cellulose fibers are strongly bonded with hydrogen bonds. In addition, the obtained CNF has problems such as uneven fiber length.

[0004] Therefore, a manufacturing method has been developed in which a chemical treatment step is carried out to disintegrate the cellulose fibers that make up the pulp to a certain degree before carrying out the mechanical fiberization step (Patent Documents 1 to 4). This manufacturing method makes it possible to obtain CNFs with less energy than a manufacturing method in which pulp is directly mechanically treated. Moreover, it has the advantage of being able to suppress the variation in size of the obtained CNFs. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-43677 A [Patent Document 2] JP 2017-8472 A [Patent Document 3] JP 2017-25240 A [Patent Document 4] JP 2017-25468 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, fine cellulose fibers such as CNF obtained by conventional methods have the problem that the dispersion has a high viscosity and is difficult to handle.

[0007] Therefore, an object of the present invention is to provide fine cellulose fibers that are easy to handle. [Means for solving the problem]

[0008] In order to achieve the above object, the fine cellulose fiber of the present invention is A fine cellulose fiber obtained by finely pulverizing cellulose fibers, At least a portion of the hydroxyl groups of the fine cellulose fibers are substituted with sulfate ester groups, 100 g of the 1% by mass aqueous dispersion of the fine cellulose fibers was sealed in a 100 mL centrifuge tube, left to stand at 20° C. for 24 hours, shaken in a substantially horizontal direction at 20° C. and 300 rpm for 5 minutes or more, and then rotated at 20° C. and 1 rpm for 3 minutes using a B-type viscometer to measure the viscosity μ 1 However, it is less than 100,000 mPa·s. Effect of the Invention

[0009] The fine cellulose fibers of the present invention have excellent handleability because the viscosity of the dispersion is reduced by slightly shaking the dispersion. [Brief description of the drawings]

[0010] [Figure 1] Fig. 1 shows a centrifuge tube in which an aqueous dispersion of fine cellulose fibers of the present invention is sealed, and a shaker in which the centrifuge tube is fixed on a top plate. Fig. 1A and Fig. 1B show photographs of the centrifuge tube and the shaker when observed from the horizontal and vertical directions, respectively. [Diagram 2] FIG. 2 is a graph showing the relationship between the shaking time and the viscosity of the aqueous dispersion of fine cellulose fibers of the present invention.

[0011] Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. All patents, applications and other publications and information referenced herein are incorporated herein by reference in their entirety. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Microfine cellulose fiber] The fine cellulose fibers of the present invention are fine cellulose fibers obtained by pulverizing cellulose fibers, and at least a part of the hydroxyl groups of the fine cellulose fibers are substituted with sulfate ester groups. The viscosity of the fine cellulose fibers of the present invention is reduced by slightly shaking the dispersion. Therefore, the viscosity of the fine cellulose fibers of the present invention is reduced by, for example, the impact when the dispersion is poured into a container, and therefore the fibers are easy to handle. Specifically, the viscosity μ of the fine cellulose fibers of the present invention is measured by sealing 100 g of a 1% by mass aqueous dispersion of the fine cellulose fibers in a 100 mL centrifuge tube, leaving the dispersion at 20° C. for 24 hours, shaking the dispersion at 20° C. and 300 rpm for 5 minutes or more in a substantially horizontal direction, and then rotating the dispersion at 20° C. and 1 rpm for 3 minutes using a B-type viscometer. 1 However, it is less than 100,000 mPa·s.

[0013] The viscosity μ 1 The lower limit of the viscosity μ is not particularly limited, but is, for example, 20,000 mPa·s or more. 1 may be, for example, 20,000 mPa·s to 100,000 mPa·s, 30,000 mPa·s to 100,000 mPa·s, 40,000 mPa·s to 100,000 mPa·s, 50,000 mPa·s to 100,000 mPa·s, or 60,000 mPa·s to 100,000 mPa·s.

[0014] Any centrifuge tube may be used, for example, Model No. 2355-100N manufactured by AGC Technos IWAKI Co., Ltd. The shaking is preferably performed using a shaker, for example, Lab Shaker (reciprocating motion) (Model No. SR-1) manufactured by AS ONE Co., Ltd.

[0015] The viscosity μ 1 The measurement of the viscosity μ is preferably started within 5 seconds after the shaking is stopped. 1 However, as time passes after shaking is stopped, the viscosity gradually returns to the original viscosity before shaking; reliability of the measured values ​​must be ensured by making the measurement conditions as uniform as possible between samples; and experimental operations actually require a certain amount of time.

[0016] The viscosity μ of the fine cellulose fiber of the present invention is measured by sealing a 1% by mass aqueous dispersion of the fine cellulose fiber in the centrifuge tube, leaving it to stand at 20° C. for 24 hours, and rotating it at 1 rpm at 20° C. for 3 minutes without shaking using a B-type viscometer. 0 may be 170,000 mPa·s or more.

[0017] The fine cellulose fiber of the present invention has a viscosity of μ 1 and μ 0 However, the following formula (1): 0.1≦μ 1 / μ 0 ≦0.5 (1) The above condition may be satisfied.

[0018] The fine cellulose fiber of the present invention has at least a part of its hydroxyl groups substituted with sulfate ester groups. Specifically, the fine cellulose fiber has at least a part of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer in which D-glucose is bonded via β(1→4) glucoside bond) constituting the fiber substituted with sulfate ester groups represented by formula (2).

[0019] (-OSO 3 - ) rZ r+ (2) In formula (2), r is an independent natural number from 1 to 7, Z r+ When r=1, it is at least one selected from the group consisting of a hydrogen ion, an alkali metal ion, a monovalent transition metal ion, an ammonium ion, an aliphatic ammonium ion, an aromatic ammonium ion, and a cationic polymer, and when r=2 or more, it is at least one selected from the group consisting of an alkaline earth metal ion, a polyvalent metal ion, and a compound containing two or more cationic functional groups (e.g., diamine, etc.) in the molecule.

[0020] The fine cellulose fibers of the present invention have sulfate ester groups, which improves the hydrophilicity of the fibers. That is, by introducing sulfate ester groups into the fine cellulose fibers, the dispersibility of the fine cellulose fibers when dispersed in a dispersion liquid can be improved. Moreover, the electronic repulsion of the introduced sulfate ester groups makes it easier to maintain the dispersed state in the dispersion liquid.

[0021] In addition, the fine cellulose fibers can be imparted with a physiological activity derived from sulfate ester groups. For example, chondroitin sulfate, a type of sulfated polysaccharide known as a heparin-like substance, has hyaluronidase inhibitory activity and skin moisturizing activity, and therefore its application to xerosis, asteatosis, and atopic dermatitis is being considered. The fine cellulose fibers of the present invention can also be used in the medical field based on the physiological activity derived from sulfate ester groups.

[0022] The dispersion medium of the dispersion liquid is not particularly limited. For example, as an aqueous dispersion medium, water (e.g., ion-exchanged water, distilled water, pure water, tap water, etc., the same applies below), alcohol, ketone, amine, carboxylic acid, ether, amide, etc., or a mixture thereof, etc., may be used.

[0023] (Amount of sulfate ester groups introduced into fine cellulose fibers) The amount of sulfuric acid ester groups introduced into the fine cellulose fiber of the present invention can be expressed as the amount of sulfur introduced based on the sulfate ester groups, and is not particularly limited, but is preferably within a range in which transparency and dispersibility can be maintained to a certain degree. The amount of sulfur introduced per 1 g (mass) of the fine cellulose fiber of the present invention is, for example, higher than 0.4 mmol / g, and is 0.42 mmol / g to 9.9 mmol / g, 0.5 mmol / g to 9.9 mmol / g, or 0.6 mmol / g to 9.9 mmol / g.

[0024] If the amount of sulfur introduced is more than 0.42 mmol / g, the hydrogen bonds between the fibers do not become too strong, and dispersibility tends to improve, and if it is 0.5 mmol / g or more, the electronic repulsion can be made stronger, making it easier to maintain a stable dispersed state. On the other hand, if the amount of sulfur introduced is 9.9 mmol / g or less, the decrease in crystallinity and the increase in cost when introducing sulfur can be suppressed.

[0025] In particular, when attention is paid to maintaining dispersibility and transparency, the amount of sulfur introduced is, for example, more than 0.42 mmol / g and not more than 3 mmol / g, 0.5 mmol / g to 3 mmol / g, 0.5 mmol / g to 2 mmol / g, or 0.5 mmol / g to 1.5 mmol / g.

[0026] (Method for measuring the amount of sulfate ester groups introduced) The amount of sulfur introduced into the fine cellulose fiber of the present invention (i.e., the amount of sulfate ester groups introduced) can be measured by a CHNS / O elemental analyzer. The amount of sulfur introduced can also be calculated by measuring electrical conductivity. When the fine cellulose fiber is prepared from pulp into which sulfate ester groups have been introduced (hereinafter referred to as "sulfate ester group-introduced pulp"), the amount of sulfur introduced may be determined from the amount of sulfur introduced into the pulp.

[0027] The average fiber length and average fiber width of the fine cellulose fiber of the present invention are not particularly limited, but are preferably adjusted so that the fibers are easily entangled with each other and are easily transparent when dispersed in an aqueous dispersion medium.

[0028] (Average fiber length of fine cellulose fibers) The average fiber length of the fine cellulose fibers of the present invention can be indirectly expressed, for example, by the degree of polymerization. The average fiber length of the fine cellulose fibers of the present invention is, for example, 280 or more, 300-1000, or 300-600 in terms of the degree of polymerization.

[0029] When the degree of polymerization of the fine cellulose fiber of the present invention is 280 or more, it is possible to prevent the fiber from becoming weakly entangled due to a decrease in fiber length. On the other hand, when the degree of polymerization of the fine cellulose fiber of the present invention is 600 or less, the fiber has high dispersibility, and when slurried, the slurry viscosity does not become too high, resulting in high dispersion stability and excellent handleability.

[0030] (Method of measuring degree of polymerization) The method for measuring the degree of polymerization is not particularly limited, but for example, the copper ethylenediamine method can be used. Specifically, the degree of polymerization of the fine cellulose fiber of the present invention can be measured by dissolving the fine cellulose fiber of the present invention in a 0.5 M copper ethylenediamine solution and measuring the viscosity of the solution by a viscometer.

[0031] (Average fiber width of fine cellulose fibers) The average fiber width of the fine cellulose fiber of the present invention is not particularly limited, but is preferably a width that easily provides transparency when dispersed in an aqueous dispersion medium. The average fiber width of the fine cellulose fiber of the present invention is, for example, 1 nm to 1000 nm, 2 nm to 500 nm, 2 nm to 100 nm, 2 nm to 30 nm, or 2 nm to 20 nm when observed with an electron microscope.

[0032] If the average fiber width is 1 nm or more, the physical properties (strength, rigidity, dimensional stability, etc.) of fine cellulose fibers are easily exhibited when dispersed in water as cellulose molecules. On the other hand, if the average fiber width is 1000 nm or less, the physical properties (transparency, strength, rigidity, dimensional stability, etc.) of fine cellulose fibers tend to be easily obtained.

[0033] In particular, from the viewpoint of applications requiring ease of handling and transparency, the average fiber width is, for example, within the following range. If the average fiber width is less than 30 nm, the aspect ratio does not decrease, and there is a tendency to avoid a decrease in entanglement between fibers. Furthermore, if the average fiber width is less than 30 nm, it is far from 1 / 10 of the wavelength of visible light, and when combined with a matrix material, refraction and scattering of visible light are unlikely to occur at the interface, and scattering of visible light does not occur, and transparency tends to increase. Therefore, from the viewpoint of ease of handling and transparency, the average fiber width of the fine cellulose fiber of the present invention is, for example, 2 nm to 30 nm, 2 nm to 20 nm, or 2 nm to 10 nm. In particular, from the viewpoint of transparency, the average fiber width of the fine cellulose fiber of the present invention is, for example, 20 nm or less, or 10 nm or less. If the average fiber width is 10 nm or less, scattering of visible light can be reduced, and therefore fine cellulose fibers having high transparency can be obtained.

[0034] (Method of measuring average fiber width) The average fiber width of the fine cellulose fibers of the present invention can be measured using a known technique. For example, fine cellulose fibers are dispersed in a dispersion medium such as pure water to prepare a dispersion liquid with a predetermined mass %. Then, this dispersion liquid is spin-coated on a silica substrate coated with PEI (polyethyleneimine), and the fine cellulose fibers on the silica substrate are observed. For example, a scanning probe microscope (for example, SPM9700 manufactured by Shimadzu Corporation) can be used as an observation method. The average fiber width of the fine cellulose fibers can be obtained by randomly selecting 20 fine cellulose fibers in the obtained observation image, measuring the fiber width of each fiber, and averaging them.

[0035] (Haze value) The transparency when visually observing a dispersion liquid adjusted to a predetermined solid content concentration of the fine cellulose fibers of the present invention can be evaluated by the haze value. The solid content concentration is not particularly limited, but is, for example, 0.1% by mass to 20% by mass. From the viewpoint of transparency, it is preferable that the haze value of such a dispersion liquid is 20% or less. When the solid content concentration is 0.2% by mass to 0.5% by mass, the haze value of this dispersion liquid is, for example, 20% or less, 15% or less, or 10% or less.

[0036] The dispersion medium of the dispersion liquid is, for example, an aqueous dispersion medium. Examples of the aqueous dispersion medium that can be used include water, alcohol, ketone, amine, carboxylic acid, ether, amide, and mixtures thereof.

[0037] (Method of measuring haze value) The haze value can be measured, for example, as follows: Fine cellulose fibers are dispersed in the dispersion medium to a predetermined solid content concentration. The haze value can be obtained by measuring the dispersion liquid using a spectrophotometer in accordance with JIS K 7105.

[0038] (Total light transmittance) The total light transmittance of the dispersion is, for example, 90% or more, 95% or more, within the above-mentioned haze value range. The total light transmittance can be measured, for example, as follows. First, fine cellulose fibers are dispersed in the dispersion medium to a predetermined solid content concentration. Then, the total light transmittance can be obtained by measuring the dispersion using a spectrophotometer in accordance with JIS K 7105.

[0039] [Method of manufacturing fine cellulose fibers] The method for producing the fine cellulose fibers of the present invention is not particularly limited, but for example, the fibers can be produced from sulfate ester group-introduced pulp by the method shown below. In the present invention, the term "sulfate ester group-introduced pulp" refers to a fibrous member formed by an assembly of a plurality of cellulose fibers, in which at least a portion of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer formed by β(1→4) glycosidic bonds between D-glucose) constituting the cellulose fibers contained therein has been substituted with sulfate ester groups.

[0040] The fine cellulose fibers of the present invention can be produced by directly subjecting a fiber raw material to a microfibrillation treatment to obtain fine cellulose fibers and then substituting at least a part of the hydroxyl groups of the cellulose constituting the fine cellulose fibers with sulfate ester groups, or by microfibrillating sulfate ester group-introduced pulp as described below. The latter method has the advantage that fine cellulose fibers can be produced by only carrying out the microfibrillation treatment step.

[0041] [Method of manufacturing sulfate ester group-introduced pulp] The sulfate ester group-introduced pulp can be obtained, for example, by the method shown below, but is not limited to this method.

[0042] In summary, this method involves subjecting a cellulose-containing fiber raw material (e.g., wood-based pulp (hereinafter simply referred to as "wood pulp")) to a chemical treatment to produce sulfate ester group-introduced pulp. This chemical treatment process includes a contacting step in which the fiber raw material is contacted with a sulfate ester group-donor compound described below and urea or a urea derivative (hereinafter referred to as "urea, etc."), and a reaction step in which the fiber raw material after this contacting step is subjected to a heating reaction to substitute at least a portion of the hydroxyl groups of the cellulose with sulfate ester groups.

[0043] In this specification, the fiber raw material refers to fibrous pulp containing cellulose molecules. Pulp is a fibrous member in which a plurality of cellulose fibers are assembled. The cellulose fiber is an assembly of a plurality of fine fibers (e.g., microfibrils, etc.). The fine fiber is an assembly of a plurality of cellulose molecules (hereinafter, sometimes simply referred to as "cellulose"), which are chain-like polymers in which D-glucose is bonded via β(1→4) glycoside bonds. In addition, it is preferable to wash the fiber raw material in advance. For example, by filtering and dehydrating the material using water on a 200 mesh or 235 mesh sieve, it is possible to sieve out fine fibers and debris that are too fine, which is desirable because it improves the handling during production. In other words, pulp is a fiber in which cellulose fibers of a size that can become residues of 200 mesh or 235 mesh are assembled.

[0044] (Textile raw materials) The fiber raw material used in this method is not particularly limited as long as it contains cellulose as described above, and for example, what is generally called pulp may be used, or what contains cellulose isolated from sea squirts, seaweed, etc., and any material may be used as long as it is composed of cellulose molecules. Examples of the pulp include, but are not limited to, cotton-based pulps such as wood pulp, dissolving pulp, and cotton linter, non-wood-based pulps such as straw, bagasse, paper mulberry, mitsumata, hemp, kenaf, and fruit, and waste paper pulps prepared from waste newspapers, waste magazines, waste cardboard, etc. Note that, from the viewpoint of ease of availability, wood pulp is easy to use as the fiber raw material.

[0045] There are various kinds of wood pulp, but the use is not particularly limited, and examples thereof include paper pulp such as softwood kraft pulp (NBKP), hardwood kraft pulp (LBKP), thermomechanical pulp (TMP), etc. When the pulp is used as a fiber raw material, one type of pulp may be used alone, or two or more types of pulp may be used in combination.

[0046] The sulfate ester group donating compound is not particularly limited as long as it is a compound capable of donating sulfate ester groups to fiber raw materials, and examples thereof include sulfamic acid, sulfamic acid salts, and sulfuryl compounds having a sulfonyl group with two oxygen atoms covalently bonded to sulfur, and these compounds may be used alone or in combination of two or more. The sulfate ester group donating compound is preferably sulfamic acid, since it has a lower acidity than sulfuric acid and has a higher efficiency of introducing sulfate ester groups, is inexpensive, and is highly safe. Hereinafter, an example will be described in which sulfamic acid is used as the sulfate ester group donating compound and urea is used as the urea.

[0047] (Contact process) The contact step is a step of contacting a fiber raw material containing cellulose with sulfamic acid and urea. This contact step is not particularly limited as long as it is a method that can cause the contact. For example, the fiber raw material may be immersed in a reaction solution in which sulfamic acid and urea are dissolved in a solvent to impregnate the fiber raw material with the reaction solution, or the reaction solution may be applied to the fiber raw material, or sulfamic acid and urea may be separately applied to, impregnated into, or sprayed onto the fiber raw material. Among these, if a method of immersing the fiber raw material in the reaction solution to impregnate the fiber raw material with the reaction solution is used, sulfamic acid and urea can be contacted uniformly with the fiber raw material.

[0048] The solvent for dissolving sulfamic acid and urea is not particularly limited, and examples thereof include protic polar solvents such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, and aqueous ammonia, aprotic polar solvents such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), and dimethylacetamide (DMA), and non-polar solvents such as diethyl ether, benzene, toluene, hexane, chloroform, and 1,4-dioxane. The solvent may be used alone or in combination of two or more. In particular, water is preferred from the viewpoint of easily dissolving sulfamic acid and urea.

[0049] In addition, the fiber raw material that has been brought into contact with sulfamic acid and urea through this contacting step is sometimes called "reaction liquid-impregnated fiber."

[0050] (Mixing ratio of reaction solution) When using a method in which the fiber raw material is immersed in the reaction solution to impregnate the fiber raw material with the reaction solution, the mixture ratio of sulfamic acid and urea contained in the reaction solution is not particularly limited.

[0051] (Contact amount of reaction solution) In contacting the fiber raw material with the reaction solution, it is preferable to make the sulfamic acid and urea in the reaction solution have a predetermined ratio relative to the fiber raw material. Specifically, the reaction solution is contacted so that the amount of sulfamic acid and the amount of urea in the reaction solution are appropriate relative to the fiber raw material in the reaction solution-impregnated fiber to be subjected to the reaction step. More specifically, the contact amount of sulfamic acid relative to the fiber raw material (solid mass, which is the dry mass) in the reaction solution-impregnated fiber immediately before being subjected to the heating reaction in the reaction step is adjusted to be equal to or greater than the contact amount of urea.

[0052] For example, the reaction liquid is prepared so that the mixing ratio of sulfamic acid and urea, in terms of mass ratio, is such that the value obtained by dividing the mass parts of sulfamic acid per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction by the mass parts of urea per 100 mass parts of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction (sulfamic acid / urea) is 0.8 or more, 0.85 or more, or 1 or more.

[0053] Also, for example, the contact amount of sulfamic acid is adjusted to be 70 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more per 100 parts by mass of the solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction.

[0054] For example, the contact amount of urea, i.e., the contact amount of urea relative to the mass of solid content of the fiber raw material in the reaction liquid-impregnated fiber immediately before being subjected to the heating reaction, is adjusted to 20 parts by mass or more, 30 parts by mass or more, or 50 parts by mass or more relative to 100 parts by mass of solid content of the fiber raw material while maintaining the above-mentioned relationship with sulfamic acid. The upper limit of the contact amount of urea is not particularly limited, but is, for example, 350 parts by mass or less, 300 parts by mass or less, or 250 parts by mass or less relative to 100 parts by mass of solid content of the fiber raw material.

[0055] Therefore, for example, by adjusting the content (mixing ratio) of urea in the reaction solution to be within the following ranges while satisfying sulfamic acid / urea ≧0.8 in relation to sulfamic acid, the transparency of the resulting sulfate ester group-introduced pulp can be appropriately improved. For example, the mixing ratio of urea is adjusted to be 20 parts by mass to 350 parts by mass, 20 parts by mass to 300 parts by mass, or 20 parts by mass to 250 parts by mass, assuming that sulfamic acid is 70 parts by mass to 350 parts by mass per 100 parts by mass of the solid content of the fiber raw material in the reaction solution-impregnated fiber immediately before being subjected to the heat reaction.

[0056] Also, for example, when the mixing ratio of sulfamic acid is 150 to 250 parts by mass per 100 parts by mass of the solid content of the fiber raw material in the reaction solution impregnated fiber immediately before the heating reaction, the reaction solution may be prepared so that the mixing ratio of urea is 20 to 250 parts by mass per 100 parts by mass of the solid content of the fiber raw material in the reaction solution impregnated fiber immediately before the heating reaction. In this case, the transparency of the obtained sulfate ester group-introduced pulp can be more appropriately improved.

[0057] The contact amounts of sulfamic acid and urea per 100 parts by mass of the solid content of the fiber raw material can be appropriately calculated depending on, for example, the state of the reaction solution-impregnated fiber to be subjected to the reaction step.

[0058] (State of fiber impregnated with reaction liquid) The state of the reaction liquid-impregnated fiber to be subjected to the above-mentioned next reaction step may be, for example, the reaction liquid-impregnated fiber as it is, i.e., a state in which the fiber raw material is in contact with the reaction liquid without actively removing water, or a state in which the fiber raw material is in contact with the reaction liquid and the water has been actively removed, etc.

[0059] The former reaction liquid-impregnated fibers (in a state where water is not actively removed) include fibers in a state where the fiber raw material is in contact with the reaction liquid (including, for example, a slurry state, etc.), and fibers prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and leaving it to stand.

[0060] On the other hand, the latter reaction liquid-impregnated fiber (in a state where moisture has been actively removed) refers to a fiber in which moisture has been intentionally removed from a state where the fiber raw material is in contact with the reaction liquid. For example, it includes a fiber prepared by removing the fiber raw material from the state where the reaction liquid is in contact with the fiber raw material and naturally drying it by air drying or the like, a fiber prepared by filtering and dehydrating the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material, a fiber prepared by further air drying the filtered and dehydrated material, a fiber prepared by further drying the filtered and dehydrated material using a circulating air dryer, a fiber prepared by further drying the filtered and dehydrated material using a heating dryer, a fiber prepared by drying the fiber raw material in a state where the reaction liquid is in contact with the fiber raw material using a circulating air dryer or a heating dryer, and the like.

[0061] In this way, the reaction liquid-impregnated fiber to be subjected to the reaction step may be one that has not been subjected to the active water removal as described above, or one that has been actively removed to remove a certain amount of water. In addition, when removing water by drying, there is no particular problem even if the moisture content after drying is about 1%. In particular, by using the latter method, the moisture content in the reaction liquid-impregnated fiber to be subjected to the reaction step can be reduced, so that the reaction time in the heating reaction in the reaction step can be shortened. This has the advantage of improving the productivity of the sulfate ester group-introduced pulp. In addition, by using the method of performing a dehydration treatment, there is the advantage that the reaction liquid-impregnated fiber can be prepared more efficiently than when a large amount of reaction liquid is treated.

[0062] When an active drying method is used, the moisture content of the reaction solution-impregnated fibers may be reduced to about 1%, or the moisture may be removed by drying the fibers to an absolutely dry state with a moisture content significantly lower than 1%.

[0063] In this specification, the term "wet state" refers to a fiber that is impregnated with the reaction liquid and has a moisture content of 1% or more, and is not in an absolute dry state. For example, the term "wet state" may refer to fibers that are impregnated with the reaction liquid, fibers that have been dehydrated to a certain extent, and fibers that have been dried to a certain extent.

[0064] In addition, in this specification, bone dry means a state in which the moisture content is reduced to less than 1% by, for example, reducing the pressure in a desiccator containing a desiccant such as calcium chloride or diphosphorus pentoxide, or by subjecting the material to a long-term heat drying treatment.

[0065] Therefore, when the latter method (reaction method in a state where active moisture removal is performed) is used in the contact step, a method for bringing the moisture content of the reaction liquid-impregnated fiber to a non-absolutely dry state may be used, or a method for bringing the moisture content to an absolute dry state may be used, but it is preferable to use a method for bringing the moisture content to a non-absolutely dry state.

[0066] In this specification, the moisture content of the reaction liquid-impregnated fiber is calculated using the following formula. Moisture content of reaction liquid-impregnated fiber (%) = 100 - (mass of solids in reaction liquid-impregnated fiber (g) / reaction liquid-impregnated fiber at the time of moisture content measurement (g)) x 100 = {(reaction liquid-impregnated fiber at the time of moisture content measurement (g) - solids in reaction liquid-impregnated fiber (g)) / reaction liquid-impregnated fiber at the time of moisture content measurement (g)} x 100

[0067] The solid content mass (g) in the reaction liquid-impregnated fiber in the above formula refers to the dry mass of the reaction liquid-impregnated fiber. Specifically, it refers to the dry mass adjusted to a constant weight by drying the sample at 105°C using a dryer or the like. For example, by putting the reaction liquid-impregnated fiber in a dryer and drying it under a specified drying condition (for example, a temperature of 105°C for 2 hours) and measuring the mass, the mass of the dried product after moisture has been removed from the reaction liquid-impregnated fiber (i.e., the mass of the product that is not removed under the drying condition. For example, the mass of the product containing the fiber raw material and the reagent in the reaction liquid) can be calculated. In addition, the constant weight means a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to enter or leave the facility. Specifically, it means a state in which the change in the mass between two consecutive measurements after drying for a certain period of time (for example, 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be at least half the drying time required for the first measurement).

[0068] The state of the fiber raw material when it is brought into contact with the reaction liquid is not particularly limited, and may be, for example, in a dry state or a wet state (i.e., a moist state).

[0069] (Pre-drying process in the contact process) In the above example, the method for preparing the reaction liquid-impregnated fiber in the contact step was described, in which the reaction liquid-impregnated fiber is prepared by actively removing moisture. When using a method for removing moisture while heating (pre-drying step) in this method (for example, when directly heating and drying the fiber raw material in the contact state with the reaction liquid, or heating and drying the dehydrated fiber), it is desirable to adjust the heating temperature to a predetermined temperature or lower. The drying temperature in this pre-drying step is not particularly limited, but is preferably adjusted to a temperature that can remove moisture contained in the reaction liquid-impregnated fiber and moisture in the surroundings, and does not cause the reaction to proceed. For example, the drying temperature in the pre-drying step can be adjusted so that the ambient temperature of the reaction liquid-impregnated fiber is 100°C or lower. On the other hand, from the viewpoint of workability, it is preferable to adjust the temperature to 50°C or higher. Therefore, the drying temperature in the pre-drying step in the contact step is preferably 50°C to 100°C, 70°C to 100°C.

[0070] (Moisture adjustment process in contact process) The contact step may include a moisture adjustment step in which the moisture content of the fiber raw material to be contacted with the reaction liquid is adjusted to fall within a predetermined range. This moisture adjustment step is a step in which the fiber raw material is adjusted by drying or humidifying so that the moisture content is a predetermined value. By including this moisture adjustment step, the moisture content in the fiber raw material when it is contacted with the reaction liquid or the like can be made somewhat uniform, which may improve product stability in continuous operation. In addition, there is an advantage in that storage properties can be improved by drying the fiber raw material to a certain degree to reduce the moisture content (for example, the moisture content is 1% to 10%).

[0071] (Reaction process) As described above, the reaction liquid-impregnated fiber prepared in the contact step is provided to the next reaction step. This reaction step is a step in which the cellulose fiber contained in the fiber raw material in the reaction liquid-impregnated fiber provided from the contact step is reacted with sulfamic acid and urea to replace at least a part of the hydroxyl groups in the cellulose fiber with sulfate ester groups of sulfamic acid, thereby introducing sulfate ester groups into the cellulose fiber contained in the fiber raw material. That is, this reaction step is a step in which a reaction is carried out to replace at least a part of the hydroxyl groups in the cellulose fiber contained in the reaction liquid-impregnated fiber with sulfate ester groups.

[0072] This reaction step is not particularly limited as long as it is a method capable of replacing at least a part of the hydroxyl groups of the cellulose fiber in the fiber raw material of the reaction liquid-impregnated fiber with sulfate ester groups, and for example, a method of promoting the reaction by heating the reaction liquid-impregnated fiber can be used. Hereinafter, the reaction will be described by taking the case where the reaction is carried out by this heating method as an example.

[0073] (Reaction temperature in the reaction process) The reaction temperature in the reaction step is not particularly limited, but is preferably a temperature at which sulfate ester groups can be introduced into the cellulose fibers constituting the fiber raw material while suppressing thermal decomposition and hydrolysis of the fibers. From the viewpoint of the transparency of the resulting sulfate ester group-introduced pulp, the atmospheric temperature of the reaction liquid-impregnated fibers subjected to the reaction step is adjusted to, for example, 100°C to 200°C, 120°C to 200°C, 120°C to 180°C, or 120°C to 160°C. If the atmospheric temperature during heating is 200°C or less, thermal decomposition and discoloration of the fibers can be suppressed. On the other hand, if the reaction temperature is 100°C or more, the transparency of the resulting sulfate ester group-introduced pulp tends to be improved.

[0074] The heater or the like used in the reaction step is not particularly limited, and for example, a heater capable of directly or indirectly heating the reaction liquid-impregnated fiber after the contact step while satisfying the above-mentioned requirements can be used, and a known dryer, reduced pressure dryer, microwave heating device, autoclave, infrared heating device, hot pressing method using a heat press machine (e.g., AH-2003C manufactured by AS ONE Co., Ltd.) can be used. In particular, from the viewpoint of operability, it is preferable to use a circulating air dryer since gas may be generated in the reaction step.

[0075] (Reaction time in the reaction process) The heating time (i.e., reaction time) when the heating method is used as the reaction step is not particularly limited, but is, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, or 15 minutes or more when the reaction temperature is adjusted to be within the above range, and from the viewpoints of operability and cost, it is 5 minutes to 300 minutes, or 5 minutes to 120 minutes.

[0076] By carrying out the above-mentioned steps, the above-mentioned sulfate ester group-introduced pulp can be produced.

[0077] (Cleaning process after reaction process) The chemical treatment process may include a washing step of washing the sulfate ester group-introduced pulp after the reaction step. The sulfate ester group-introduced pulp has an acidic surface due to the effect of sulfamic acid (sulfate ester group-donating compound). In addition, unreacted reaction liquid is still present. For this reason, if a washing step is provided to completely terminate the reaction and remove excess reaction liquid to neutralize the pulp, the handling properties can be improved.

[0078] This washing step is not particularly limited, and may be any step that can make the sulfate ester group-introduced pulp nearly neutral. For example, a method of washing the sulfate ester group-introduced pulp with pure water or the like until it becomes neutral may be used. Neutralization washing may also be performed using an alkaline solution or the like. When such neutralization washing is performed, examples of the alkaline compound contained in the alkaline solution include inorganic alkaline compounds and organic alkaline compounds. Examples of the inorganic alkaline compounds include hydroxides, carbonates, and phosphates of alkali metals. Examples of the organic alkaline compounds include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and hydroxides of heterocyclic compounds.

[0079] The method for separating the sulfate ester group-introduced pulp in the washing step is not particularly limited, and may be, for example, by filtering the sulfate ester group-introduced pulp and the washing water. For example, the sulfate ester group-introduced pulp after the reaction may be washed using a stainless steel sieve with an opening size of 243 μm (70 mesh) to 20 μm (635 mesh), 132 μm (120 mesh) to 45 μm (300 mesh), or 75 μm (200 mesh) to 45 μm (300 mesh).

[0080] [Physical properties of sulfate ester group-introduced pulp] The physical properties of the sulfate ester group-introduced pulp thus produced are not particularly limited, but are, for example, as follows.

[0081] (Amount of sulfate ester group introduced) The amount of sulfate ester groups introduced per 1 g (solid mass) of sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.8 mmol / g or more, 1 mmol / g or more, or 1.2 mmol / g or more.

[0082] Incidentally, the upper limit is not particularly limited, but from the viewpoint of suppressing fiber collapse and cost increase caused by decreased crystallinity, for example, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 9.9 mmol / g or less, 5 mmol / g or less.

[0083] In particular, from the viewpoint of transparency in a dispersion liquid dispersed in a dispersion medium, the amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.8 mmol / g to 5 mmol / g, 1 mmol / g to 5 mmol / g, or 1.2 mmol / g to 5 mmol / g per 1 g (solid content mass) of the sulfate ester group-introduced pulp.

[0084] From the viewpoint of viscosity, the sulfate ester group-introduced pulp is preferably adjusted as follows. By setting the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp within the following range, a decrease in viscosity in the dispersion can be suppressed. For example, the upper limit of the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 3.5 mmol / g or less, 2 mmol / g or less. The lower limit is, for example, 1 mmol / g or more, 1.5 mmol / g or more. For example, in the sulfate ester group-introduced pulp, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp can be adjusted to 0.8 mmol / g to 3.5 mmol / g, 1 mmol / g to 2.5 mmol / g, or 1.5 mmol / g to 2 mmol / g.

[0085] The dispersion medium constituting the dispersion liquid of the sulfate ester group-introduced pulp is not particularly limited, but is preferably one that can exhibit the transparency and viscosity as described above. For example, the dispersion medium may be a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, or ammonia water; an aprotic polar solvent such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), or dimethylacetamide (DMA); or a non-polar solvent such as diethyl ether, benzene, toluene, hexane, chloroform, or 1,4-dioxane; one of these may be used alone, or two or more may be used in combination. From the viewpoint of handling, for example, a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, or ammonia water may be used.

[0086] (Method for measuring the amount of sulfate ester groups introduced) The amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp can be evaluated based on the amount of sulfur introduced due to the sulfate ester groups, or by directly measuring the sulfate ester groups. For example, the amount of sulfate ester groups introduced into the pulp can be measured using a CHNS / O elemental analyzer. The amount of sulfate ester groups introduced into the pulp can also be calculated by measuring electrical conductivity.

[0087] (Crystallization degree) The sulfate ester group-introduced pulp may have, for example, a cellulose I-type crystal structure as a crystal structure, and the crystallinity thereof may be 75% or less. If the crystallinity of the sulfate ester group-introduced pulp is 75% or less, the transparency of the dispersion in which the sulfate ester group-introduced pulp is dispersed tends to be improved. Therefore, from the viewpoint of the transparency of the dispersion, the crystallinity of the sulfate ester group-introduced pulp is, for example, 75% or less, 73% or less, 71% or less, or 70% or less. In addition, from the viewpoint of maintaining the fiber shape, the crystallinity of the sulfate ester group-introduced pulp is preferably 30% or more. And, from the viewpoint of viscosity, the crystallinity of the sulfate ester group-introduced pulp is, for example, 70% or less, 65% or less, or 60% or less. Furthermore, from the viewpoint of handleability in the manufacturing method of the sulfate ester group-introduced pulp, the crystallinity of the sulfate ester group-introduced pulp is, for example, 30% or more, or 40% or more.

[0088] For example, sulfate ester group-introduced pulp exhibits transparency even though it has a cellulose I type crystal structure as a crystal structure. That is, sulfate ester group-introduced pulp has a function of exhibiting transparency even though it has a fibrous form of I type crystal structure. Here, water-soluble cellulose (e.g., carboxymethyl cellulose, hydroxypropyl cellulose, and cellulose sulfate) has been known as a cellulose exhibiting transparency. The crystal structures of these celluloses are all cellulose II type crystal structures, and do not have a fibrous structure. That is, the transparency of the conventional cellulose is exhibited by disintegrating the fibrous structure.

[0089] (Method of measuring crystallinity) The crystallinity of the sulfate ester group-introduced pulp can be measured, for example, by using an X-ray diffraction device.

[0090] When the amount of sulfate ester groups introduced and the degree of crystallinity of the sulfate ester group-introduced pulp are within the above-mentioned ranges, the transparency of a dispersion in which the sulfate ester group-introduced pulp is dispersed in a dispersion medium such as water can be improved.

[0091] The sulfate ester group-introduced pulp has an excellent viscosity due to, for example, a predetermined degree of crystallinity. Specifically, the viscosity of a pulp having a general I-type crystal structure is about several tens to several hundreds of mPa·s when measured by rotating at 6 rpm at 20°C for 3 minutes using a B-type viscometer, whereas the sulfate ester group-introduced pulp can exhibit an excellent viscosity (for example, several thousand mPa·s or more) that was not expected for conventional general pulps.

[0092] (transparency) The transparency in this specification can be evaluated, for example, by the total light transmittance (%), which evaluates the transparency of a liquid. Specifically, the transparency function of the sulfate ester group-introduced pulp can be evaluated by the total light transmittance (%) of a dispersion obtained by dispersing the sulfate ester group-introduced pulp in water. For example, the sulfate ester group-introduced pulp has a total light transmittance (%) of 80% or more, 85% or more, or 90% or more in an aqueous dispersion.

[0093] (Method for measuring total light transmittance) The total light transmittance can be measured, for example, using a spectroscopic haze meter.

[0094] The solid content concentration in this specification can be calculated, for example, using the following formula. Solid concentration (%) = (mass of solid content of sample (g)) / (amount of sample provided (g)) x 100

[0095] The "mass of solid content of the sample (g)" in the above formula refers to the dry mass of the sample. Specifically, it refers to the dry mass adjusted to a constant mass by drying the sample at 105°C using a dryer or the like. For example, the dispersion is placed in a dryer, dried under specified drying conditions (for example, at a temperature of 105°C for 2 hours), and the mass is measured, so that the dry mass of the sulfate ester group-introduced pulp as the sample in the dispersion can be calculated. In addition, the constant mass means a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to enter or leave. Specifically, it means a state in which the change in mass between two consecutive measurements after drying for a certain period of time (for example, 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be at least half the drying time required for the first measurement).

[0096] (average fiber length) The average fiber length of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 0.2 mm to 2 mm, 0.2 mm to 1.8 mm, 0.2 mm to 1.5 mm, or 0.2 mm to 1 mm in order to improve the transparency described above.

[0097] (Short fiber rate (%)) Furthermore, in order to improve transparency, the sulfate ester group-introduced pulp may contain pulp having a short fiber length as described below. Examples of this short fiber length pulp (hereinafter referred to as "short fiber") include pulp having a fiber length of 0.04 mm or more and 0.2 mm or less in the fiber length distribution. The content (%) of short fibers in the sulfate ester group-introduced pulp (i.e., short fiber rate (%)) is, for example, 10% or more, 15% or more.

[0098] From the viewpoints of transparency and handleability, the sulfate ester group-introduced pulp has a short fiber content (i.e., short fiber rate (%)) in terms of fiber length distribution of, for example, 10% to 70%, 10% to 60%, 10% to 50%, 10% to 45%, or 15% to 45%.

[0099] (average fiber width) The average fiber width of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 5 μm to 100 μm, 10 μm to 50 μm, 20 μm to 40 μm, or 20 μm to 30 μm.

[0100] (Fiber width distribution) In order to improve transparency, it is preferable that the sulfate ester group-introduced pulp has a high proportion of pulp with fiber widths of 1 μm to 40 μm, 1 μm to 30 μm, and 1 μm to 20 μm in its fiber width distribution.

[0101] (Method of measuring average fiber length, average fiber width and fiber distribution) The average fiber length and average fiber width of the sulfate ester group-introduced pulp can be measured, for example, using a fiber tester or fiber length distribution measuring instrument manufactured by Lorentzen & Wettley in accordance with ISO 16065-2: 2007. The fiber length distribution and fiber width distribution of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring instrument in accordance with ISO 16065-2: 2007.

[0102] (Kink) In order to improve transparency, it is preferable that the sulfate ester group-introduced pulp has little bending. Specifically, it is preferable that the sulfate ester group-introduced pulp has a low kink (1 / m) value. For example, the sulfate ester group-introduced pulp has a kink (1 / m) of 1 to 300, 1 to 100, or 1 to 50.

[0103] (Method of measuring kink) The kink of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring instrument conforming to ISO 16065-2:2007.

[0104] From the viewpoint of reliability of the measured values ​​of the sulfate ester group-introduced pulp, it is desirable to measure at least 5,000 fibers in accordance with ISO 16065-2: 2007. Moreover, the number of fibers contained in the sulfate ester group-introduced pulp is desirably 5,000 or more and 70,000 or less per 0.1 g of solid content.

[0105] (viscosity) When the degree of crystallinity of the sulfate ester group-introduced pulp is equal to or less than the aforementioned value, for example, the dispersion has a predetermined viscosity. For example, when the degree of crystallinity of the sulfate ester group-introduced pulp is 70% or less, the viscosity of the dispersion obtained by dispersing the sulfate ester group-introduced pulp in water is 1000 mPa·s or more, 5000 mPa·s or more, or 10000 mPa·s or more. In particular, when the degree of crystallinity of the sulfate ester group-introduced pulp is 60% or less, the viscosity of the dispersion tends to increase. Furthermore, when the average fiber length is 1 mm or less, this tendency becomes stronger.

[0106] (Method of measuring viscosity) The viscosity (mPa s) of the sulfate ester group-introduced pulp can be measured, for example, using a B-type viscometer at a measurement temperature of 20°C, with the measurement being performed at rotation speeds of 6 rpm and 60 rpm. The thixotropy index (TI) value can also be calculated from each viscosity value. TI value = (viscosity at 6 rpm) / (viscosity at 60 rpm)

[0107] The TI value can be adjusted as appropriate, and when a high TI value is required, the lower limit of the TI value is, for example, 3 or more, 4 or more, or 5 or more. The upper limit of the TI value is, for example, 10 or less, 8 or less, 6 or less, or 5 or less. On the other hand, when a low TI value is preferred, the lower limit is, for example, 1 or more, and the upper limit is, for example, 3 or less, or 2.5 or less.

[0108] (Method of producing fine cellulose fibers) The fine cellulose fibers of the present invention can be obtained by subjecting the sulfate ester group-introduced pulp produced as described above to a fine pulp refining treatment step.

[0109] (Micronization process) The micronization step of this method is a step of micronizing the sulfate ester group-introduced pulp to make fine fibers of a predetermined size (for example, nano-level). The processing device used in this step is not particularly limited as long as it has the above-mentioned function. For example, the processing device may be, but is not limited to, a low-pressure homogenizer, a high-pressure homogenizer, a grinder (stone-type grinder), a ball mill, a cutter mill, a jet mill, a single-screw extruder, a twin-screw extruder, an ultrasonic agitator, a household mixer, etc. Among these, it is desirable to use a high-pressure homogenizer because it can apply force evenly to the material and is excellent in homogenization.

[0110] In this step, when a high-pressure homogenizer is used, the sulfate ester group-introduced pulp is supplied in a state of being dispersed in an aqueous dispersion medium such as water. In the following, the dispersion liquid in which the sulfate ester group-introduced pulp is dispersed may be referred to as a slurry. The solid content concentration of the sulfate ester group-introduced pulp in this slurry is not particularly limited, and is, for example, 0.1% by mass to 20% by mass.

[0111] For example, if a slurry in which the solid content of sulfate ester group-introduced pulp has been adjusted to 0.5% by mass is fed to a processing device such as a high-pressure homogenizer, a dispersion liquid in which fine cellulose fibers having the same solid content are dispersed in an aqueous dispersion medium can be obtained. That is, in this case, a dispersion liquid with a solid content of 0.5% by mass can be obtained.

[0112] In addition, the water retention of the sulfate ester group-introduced pulp to be subjected to this step is not particularly limited, but is preferably adjusted so as to be easily pulverized by the above-mentioned device. For example, from the viewpoint of the efficiency of pulverization and the reduction of energy used, it is desirable to use sulfate ester group-introduced pulp prepared to have a high water retention. From this viewpoint, it is preferable to use sulfate ester group-introduced pulp prepared to have a water retention of 150% or more, 200% or more, 250% or more, 300% or more, or 500% or more. From the viewpoint of the recovery rate of fine cellulose fibers, the water retention is, for example, 10000% or less. Thus, from the viewpoint of the pulverization efficiency and the recovery rate, the water retention of the sulfate ester group-introduced pulp when subjected to this step is 150% to 10000%, 200% to 10000%, 220% to 10000%, 250% to 5000%, or 250% to 2000%. EXAMPLES

[0113] [Example 1] Preparation of sulfate ester group-introduced pulp (Pulp pretreatment) Softwood bleached kraft pulp (NBKP) (hereinafter simply referred to as "pulp") with an average fiber length of 2.54 mm manufactured by Marusumi Paper Co., Ltd. was washed with a large amount of ion-exchanged water, and then the water was removed using a sieve with an opening of 75 μm (200 mesh) to obtain wet pulp (hereinafter referred to as "wet pulp") with a solid content concentration of 25.0 mass% that had never been dried. The ion-exchanged water used had an electrical conductivity of 0.1 to 0.2 μS / cm as measured using an ion-exchanged water generator (model number: G-5DSTSET) manufactured by Organo Corporation, and hereafter this will be referred to as pure water.

[0114] (Chemical treatment process) Sulfamic acid and urea were added to a 1 L beaker containing 600 mL of pure water in a ratio of sulfamic acid (g) / urea (g) = 180 / 90, and then stirred at room temperature until completely dissolved to prepare a reaction solution. The sulfamic acid used was 99.8% purity manufactured by Fuso Chemical Co., Ltd., and the urea used was 99.0% purity, model number: special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. 400 g of the wet pulp was added to the obtained reaction solution and soaked for about 10 minutes (contact step).

[0115] (Reaction liquid impregnated pulp to be subjected to reaction process) The pulp impregnated with the reaction liquid (reaction liquid-impregnated pulp (corresponding to reaction liquid-impregnated fiber)) to be subjected to the next reaction step was prepared as follows. First, the pulp impregnated with the reaction liquid was spread out on an aluminum tray. Next, this aluminum tray was placed in a dryer in an atmosphere of 85°C and dried to prepare reaction liquid-impregnated pulp. The moisture content of this reaction liquid-impregnated pulp was 5% or less.

[0116] (Reaction process) The reaction solution-impregnated pulp was subjected to a heating reaction using a dryer. The temperature of the thermostatic chamber of the dryer was 140°C, and the heating time was 30 minutes. The reaction solution-impregnated pulp after heating was washed until it became neutral, to prepare a sulfate ester group-introduced pulp. The washing was carried out by adding a large amount of pure water to the reacted pulp to make a slurry, and then adding sodium hydrogen carbonate (manufactured by Nacalai Tesque, Inc., purity 99.5%) until no bubbles were generated to neutralize the slurry (washing step after the reaction step). The washing was carried out on a 300 mesh sieve (mesh opening 45 μm, manufactured by Sanpo Co., Ltd.).

[0117] Preparation of fine cellulose fibers The sulfate ester group-introduced pulp was subjected to defibration treatment five times using a high-pressure homogenizer (Yoshida Kikai Kogyo Co., Ltd., "Nano-Veita", pressure: 60 MPa) to obtain a 1% by mass aqueous dispersion of fine cellulose fibers.

[0118] [Example 2] Fine cellulose fibers were obtained in the same manner as in Example 1, except that in the reaction step, the temperature of the thermostatic chamber of the dryer was set to 160°C.

[0119] [Comparative Example 1] Fine cellulose fibers were obtained in the same manner as in Example 1, except that in preparing the reaction solution, sulfamic acid and urea were added in a ratio of sulfamic acid (g) / urea (g) = 60 / 60, and in the reaction process, the temperature of the thermostatic chamber of the dryer was set to 120°C.

[0120] [evaluation] The transparency (total light transmittance and haze value) of the 1 mass% aqueous dispersions of the fine cellulose fibers of Example 1, Example 2, and Comparative Example 1 was determined by measuring the dispersions using a spectrophotometer in accordance with JIS K 7105. The results are shown in Table 1. There was no significant difference in the total light transmittance and haze value between the fine cellulose fibers of Example 1, Example 2, and Comparative Example 1.

[0121] [Table 1]

[0122] Viscosity measurement of fine cellulose fibers 100 g of 1% by mass aqueous dispersion of the fine cellulose fibers of Example 1, Example 2, and Comparative Example 1 was sealed in a centrifuge tube (AGC Technoglass IWAKI, model number: 2355-100N, capacity: 100 mL, body material: PP (polypropylene), cap material: HDPE (high density polyethylene), size: 45 mm x 104 mm).

[0123] The conditions for measuring the viscosity of the aqueous dispersion are as follows. B-type viscometer (manufactured by Eiko Seiki Co., Ltd., model number: DV2T) Measurement conditions: 20° C., rotation at 1 rpm for 3 minutes, spindle RV-06, data recording method was single point.

[0124] The single point is a setting for the recording method that only obtains the value at the end of the measurement in the Brookfield viscometer. In other words, the instantaneous value 3 minutes after the start of the measurement is recorded.

[0125] The shaking conditions for the centrifuge tube in which the aqueous dispersion was sealed were as follows: First, the viscosity (μ 0 After the centrifuge tube was left to stand at 20° C. for 24 hours without shaking, the centrifuge tube was fixed to the top plate of a shaker (lab shaker (reciprocating motion), AS ONE Corporation, model number: SR-1) so that the direction of the main body (the direction perpendicular to the top surface of the cap when the cap of the centrifuge tube is closed) coincided with the direction of horizontal shaking (FIG. 1), and the tube was subjected to horizontal shaking (20° C., 300 rpm (instrument scale 10)) for 1 minute, 3 minutes, 5 minutes, 10 minutes, 15 minutes, or 20 minutes, and the viscosity (μ 1 ) was measured. Viscosity μ 1 Measurements were started within 5 seconds after shaking had stopped.

[0126] The results are shown in Table 2 and Figure 2. As the shaking time increases, the viscosity (μ 0 ) compared to the viscosity after shaking (μ 1 In particular, when the shaking time was 3 minutes or more in Example 1, and when the shaking time was 5 minutes or more in Example 2, the viscosity μ of 100,000 mPa·s or less decreased. 1 On the other hand, in Comparative Example 1, even when the shaking time was 20 minutes, the viscosity μ was far greater than 100,000 mPa·s. 1 In Example 1, when the shaking time was 3 minutes or more, the viscosity μ was 30,000 mPa·s or more and 100,000 mPa·s or less. 1 In Example 2, when the shaking time was 5 minutes or more, the viscosity μ 1 Therefore, it was found that the fine cellulose fibers of Examples 1 and 2 had excellent handleability because the viscosity of the 1% by mass aqueous dispersion of the fine cellulose fibers of Examples 1 and 2 was reduced by slightly shaking the dispersion.

[0127] [Table 2]

[0128] In addition, from the relationship between the shaking time and viscosity shown in Table 2, the shaking time and μ 1 / μ 0 The relationship between the amount of the shaking time and the amount of the sintering time was calculated. The results are shown in Table 3. As the shaking time increased, the μ 1 / μ 0 In particular, when the shaking time was 3 minutes or more in Example 1, and when the shaking time was 5 minutes or more in Example 2, the μ 1 / μ 0 On the other hand, in Comparative Example 1, even when the shaking time was 20 minutes, the μ value was far greater than 0.5. 1 / μ 0 In Example 1, when the shaking time was 3 minutes or more, the μ value was 0.1 to 0.5. 1 / μ 0 In Example 2, when the shaking time was 5 minutes or more, the μ 1 / μ 0 showed.

[0129] [Table 3]

[0130] The various features of the present invention described herein can be combined in various ways, and all aspects obtained by such combinations, including combinations not specifically described herein, are within the scope of the present invention. In addition, those skilled in the art will understand that many different modifications are possible without departing from the spirit of the present invention, and equivalents including such modifications are also included in the scope of the present invention. Therefore, it should be understood that the embodiments described herein are merely examples and are not intended to limit the scope of the present invention.

Claims

1. A fine cellulose fiber obtained by finely pulverizing cellulose fibers, At least a portion of the hydroxyl groups of the fine cellulose fibers are substituted with sulfate ester groups, 100 g of the 1% by mass aqueous dispersion of the fine cellulose fibers was sealed in a 100 mL centrifuge tube, left to stand at 20° C. for 24 hours, shaken at 300 rpm at 20° C. in a substantially horizontal direction for 5 minutes or more, and then rotated at 1 rpm at 20° C. for 3 minutes using a B-type viscometer to measure the viscosity μ 1 The fine cellulose fibers have a viscosity of 100,000 mPa·s or less.

2. The 1% by mass aqueous dispersion of the fine cellulose fibers was sealed in the centrifuge tube, allowed to stand at 20° C. for 24 hours, and then rotated at 20° C. and 1 rpm for 3 minutes without shaking using a B-type viscometer to measure the viscosity μ 0 The fine cellulose fibers according to claim 1, wherein the viscosity of the fine cellulose fibers is 170,000 mPa·s or more.

3. The viscosity μ 1 and μ 0 is expressed by the following formula (1): 0.1≦μ 1 / m 0 ≦0.5 (1) The fine cellulose fibers according to claim 2, which satisfy the above.

Citation Information

Patent Citations

  • Production method of cellulose nanofiber and production apparatus of cellulose nanofiber

    JP2017008472A

  • Method for producing cellulose nanofiber

    JP2017025240A

  • Phosphorylated fine cellulose fiber and production method thereof

    JP2017025468A

  • Method for producing cellulose nanofiber

    JP2017043677A